Differences in high on-treatment platelet reactivity between intracoronary and peripheral blood after dual anti-platelet agents in patients with coronary artery disease - Hu, Yu-Feng; Lu, Tse-Min; Wu, Cheng-Hsueh; Lin, Yenn-Jiang; Chang, Shih-Lin; Lo, Li-Wei; Tuan, Ta-Chuan; Chao, Tze-Fan; Chung, Fa-Po; Liao, Jo-Nan; Tzeng, Cheng-Hwai; Chen, Shih-Ann; Tsao, Hsuan-Ming (Thrombosis and Haemostasis, 2013)
The differences of high on-treatment platelet reactivity (HPR) between the coronary arteries and peripheral veins might be associated with poor prediction of adverse cardiovascular events in patients with coronary artery diseases. HPR from the peripheral blood might not adequately reflect the platelet responses in the coronary artery. A total of 21 patients were recruited, and regional differences in HPR were compared between blood samples from the intra-coronary artery (IC), femoral artery (FA), and femoral vein (FV) by light aggregometry (agonists: arachidonic acid, LTA-AA; ADP, LTA-ADP), VerifyNow P2Y12 assays, and a platelet function analyser (PFA-100, collagen and epinephrine cartridge, PFA-CEPI). There were regional differences in the platelet reactivities observed by LTA-AA, VerifyNow P2Y12 assays, and PFACEPI. Platelets from the IC had higher platelet reactivities than those from the FV and FA by the VerifyNow P2Y12 assays but lower reactivities by LTA-AA and PFA-CEPI. HPR values from the blood in the FA were more similar to those from the IC than those from the FV by any test. The monocyte percentages were the only factors associated with differences in HPR between the FV and IC by the VerifyNow P2Y12 assays. Triglyceride levels were associated with the differences in HPR between the FV and IC by LTA-ADP. During the six-month follow-up period, two patients developed cardiovascular events and exhibited differences in HPR between different sites by VerifyNow P2Y12 assays. In conclusions, there were regional differences in HPR in patients with coronary artery diseases, which might prevent the adequate prediction of cardiovascular events.
Keywords: High on-treatment platelet reactivity; aspirin; clopidogrel; coronary artery disease